Possible implications of dysregulated nicotinic acetylcholine receptor diffusion and nanocluster formation in myasthenia gravis - Barrantes, Francisco Jose (2021)
Myasthenia gravis is a rare and invalidating disease affecting the neuromuscular junction of voluntary muscles. The classical form of this autoimmune disease is characterized by the presence of antibodies against the most abundant protein in the neuromuscular junction, the nicotinic acetylcholine receptor. Other variants of the disease involve autoimmune attack of non-receptor scaffolding proteins or enzymes essential for building or maintaining the integrity of this peripheral synapse. This review summarizes the participation of the above proteins in building the neuromuscular junction and the destruction of this cholinergic synapse by autoimmune aggression in myasthenia gravis. The review also covers the application of a powerful biophysical technique, superresolution optical microscopy, to image the nicotinic receptor in live cells and follow its motional dynamics. The hypothesis is entertained that anomalous nanocluster formation by antibody crosslinking may lead to accelerated endocytic internalization and elevated turnover of the receptor, as observed in myasthenia gravis.